Elevated protein carbonyl and HIF‐1α levels in eyes with proliferative diabetic retinopathy. (29th May 2013) - Loukovaara, Sirpa; Koivunen, Peppi; Inglés, Marta; Escobar, Javier; Vento, Maximo; Andersson, Sture
Abstract. Purpose: To evaluate the role of protein carbonyls and hypoxia inducible factor‐1α (HIF‐1α) in diabetic eyes with proliferative diabetic retinopathy (PDR). Methods: Prospective consecutive controlled observational study was performed. Vitreous samples were collected at the start of the 3‐ppp vitrectomy. Protein carbonylation analysis was performed by Western blotting with antibody against 2, 4‐Dinitrophenol (anti‐DNP), following derivatization of protein carbonyls with 2, 4 Dinitrophenylhydrazine (DNHP). Protein carbonylation was quantified by scanning densitometry analysis and relativized to the total amount of protein into the ponceau staining of membranes. Vitreous HIF‐1 α was determined with ELISA in a subgroup of the samples. Thirty‐one eyes were operated due to PDR (study group). Of the 189 controls, 39 had nonproliferative diabetic retinopathy (non‐PDR), 111 retinal detachment (RD) and 39 macular hole/pucker (MH). Results: Comparison of eyes with PDR with controls revealed that the mean vitreous concentrations of protein carbonyls were significantly higher in the eyes affected with PDR being 242 ± 130 (SD) compared with non‐PDR controls 180 ± 142, nondiabetic eyes affected with RD 175 ± 131 and MH/pucker 140 ± 95 (p = 0.008, one‐way anova). Mean HIF‐1α values were higher in eyes with PDR compared with controls (RD, MH/pucker); the values being 0.53 ± 0.34 (SEM; n = 4) and 0.13 ± 0.04 (SEM; n = 19), respectively (p = 0.009). Conclusions: Protein carbonyl and HIF‐1 α levels were significantly increased in the vitreous fluid of surgically treated eyes with PDR. Our findings suggest an association between increased intravitreal levels of protein carbonyls and the pathogenesis of PDR.